A comprehensive review on the use of biodiesel for diesel engines - Van Giao Nguyen; Minh Tuan Pham; Nguyen Viet Linh Le; Huu Cuong Le; Thanh Hai Truong; Dao Nam Cao (International Journal of Renewable Energy Development, 2023)
Fossil fuels are the main source of energy for transportation operations around the world. However, fossil fuels cause extremely negative impacts on the environment, as well as uneven distribution across countries, increasing energy insecurity. Biodiesel is one of the potential and feasible options in recent years to solve energy problems. Biodiesel is a renewable, low-carbon fuel source that is increasingly being used as a replacement for traditional fossil fuels, particularly in diesel engines. Biodiesel has several potential benefits such as reducing greenhouse gas emissions, improving air quality, and energy independence. However, there are also several challenges associated with the use of biodiesel including the compatibility of biodiesel with existing engine technologies and infrastructure as well as the cost of production, which can vary depending on factors such as location, climate, and competing uses for the feedstocks. Meanwhile, studies aimed at comprehensively assessing the impact of biodiesel on engine power, performance, and emissions are lacking. This becomes a major barrier to the dissemination of this potential energy source. Therefore, this study will provide a comprehensive view of the physicochemical properties of biodiesel that affect the performance and emission properties of the engine, as well as discuss the difficulties and opportunities of this potential fuel source.